Expression of platelet derived growth factor B chain and beta receptor in human coronary arteries after percutaneous transluminal coronary angioplasty: an immunohistochemical study. - Tanizawa, S. (1996)
OBJECTIVE: To evaluate whether expression of platelet derived growth factor B (PDGF-B) protein is associated with expression of its receptor protein in human coronary arteries after angioplasty and to identify cells involved. BACKGROUND: PDGF is considered an important growth factor in the repair process of the vessel wall after angioplasty. In situ hybridisation has revealed expression of PDGF-A and -B chain messenger ribonucleic acid (mRNA) in human coronary arteries at sites of postangioplasty injury. METHODS: Target and non-target sites of eight coronary arteries were studied immunohistochemically for PDGF-B and PDGF-beta receptor proteins in relation to macrophages, T lymphocytes, smooth muscle cells, and HLA-DR positive cells. RESULTS: The PDGF-B and PDGF-beta receptor proteins were expressed in areas with distinct repair, containing alpha actin negative spindle cells, macrophages and, at later stages, alpha actin positive smooth muscle cells as well. When the neointima was composed mainly of alpha actin smooth muscle cells, PDGF-B expression was rare and PDGF-beta receptor expression was negative. CONCLUSIONS: There is expression of PDGF-B and PDGF-beta receptor proteins at sites of postangioplasty repair in human coronary arteries. The associated cells are mainly macrophages and alpha actin negative spindle cells; the latter may be dedifferentiated smooth muscle cells. A link between PDGF expression and the postangioplasty time interval suggests a relation with cell differentiation as part of the maturation of the repair tissue. Mutual expression of both the growth factor and its receptor protein strongly suggests that in humans a PDGF mediated repair process occurs, with involvement of smooth muscle cells and macrophages.